THE CHARACTER AND MORAL VALUE IN “LES MISERABLES” BY VICTOR HUGO - Neindisa Radike; Merry Lapasau (Universitas Indraprasta PGRI, 2020)
Abstract: The objective of this research is to find out character and moral value in the novel. The method that is used in the research is qualitative that aims to describe the character and moral value in the novel “Les Miserables”. The writer did several steps of extracting the data through reading a whole book carefully, categorizing the characters and kinds of moral values, making table based on the specifications of character and moral value. The findings reveal that there are several characters and moral values presented explicity themselves. This novel has two objectives: to explain about characters in the novel and analyze about moral value in the novel. 1) One of characters that is more dominant is lover. The value of lover reaches 18.5 % because this novel shows more about love and compassion. 2) Moral values in “Les Miserables”, there are four types of moral value such as love and sincerity, forgiveness, sacrifice, and justice/injustice. Love and sincerity is more dominant than the other elements. The value for love and sincerity reach 42% because it shows more about love and sincerity. Key words: Character, Moral value, Novel.